Does isolation from immigrant students benefit or harm third-plus generation students? - Pivovarova, Margarita; Powers, Jeanne M. (Education Policy Analysis Archives, 2019)
Enforcing and expanding immigration restrictions have been at the forefront of the Trump administration’s agenda since his inauguration in January 2017. Underlying these policies is an assumption that immigrants harm U.S. citizens. More specifically, both authorized and undocumented immigrants are framed as consuming a disproportionate share of social benefits. We used data from the 2012 Programme for International Student Assessment (PISA) to assess this claim in U.S. high school contexts, focusing on the mathematics achievement of third-plus generation students who did not attend schools with immigrant students. On average, the third-plus-generation students who did not attend schools that enrolled first or second generation immigrant students had lower achievement than their same generation peers attending schools that served immigrant students. We conclude by highlighting the research and policy implications of our findings.